Immobilized boronic acid for Suzuki–Miyaura coupling: application to the generation of pharmacologically relevant molecules - Martínez Amezaga, Maitena (2017)
Fil: Fil: Martínez Amezaga, Maitena. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Química Rosario (IQUIR -CONICET); Argentina.